Evaluación del efecto probiótico sobre la calidad de la canal y parámetros tecnológicos de la carne cuy (Cavia porcellus) - Muñoz Alvear, Erika Carolina (2024)
Studies conducted in Ecuador have examined the quality of guinea pig meat and the impact of efficient microorganisms like lactic acid bacteria and yeasts on animal nutrition, demonstrating their ability to enhance meat quality and food safety. The use of growth-promoting antibiotics (GPA) has been common in developing countries to increase production and prevent diseases, but their misuse has led to bacterial resistance and accumulation of residues in tissues, posing a risk to human health. Considering this issue, probiotics emerge as a viable alternative. Therefore, this research aims to evaluate the inclusion of lactic acid bacteria and yeasts in the diet of guinea pigs, focusing on carcass quality and technological parameters of the meat. A total of 40 animals were used, distributed into four groups: control (C), bacteria (B), yeasts (Kf), and bacteria + yeasts (B + Kf). The animals were subjected to standardized procedures for cutting, dissection, water holding capacity (WHC), color, and pH. Data were recorded in logbooks and analyzed using a simple ANOVA in SAS (v. 11). The results indicate that probiotics in guinea pig diets improved carcass quality, with the group consuming the diet with K. fragilis yeasts benefiting the most in terms of live weight and carcass yield. The WHC was higher in the group fed with bacteria, and lower losses due to freezing were observed in the group receiving the mixed culture.